Variations in Milling Time and Their Impact on the Bio-Calcium Properties of Red Snapper Fish Bones - Anggraeni, Novia; Dewi, Eko Nurcahya; Susanto, Antonius Budi; Riyadi, Putut Har (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Calcium is a macromineral essential by human body, with deficiencies often leading to bone-related issues. Red snapper bone waste is a source of calcium. The bioavailability of calcium is maximized when present in microscopic particles, such as bio-calcium. This study aims to identify the optimal milling time to produce bio-calcium from red snapper bones, evaluating parameters such as water content, particle size, and yield. Biocalcium was extracted from red snapper bone meal using a 1 N NaOH solution (1:3 ratio) with milling times of 1, 2, and 3 h. Analysis of the red snapper bone meal including yield, particle size, chemical composition, calcium, and phosphorus content. The bio-calcium was characterized based on water content, particle size, yield, Fourier-transform infrared spectroscopy (FTIR), and morphological structure using a scanning electron microscope (SEM). The results demonstrated that a 3-hour milling time yielded bio-calcium with a particle size of 410.8 nm, a water content of 4.51 ± 0.15%, and a yield of 4.12 ± 0.03%. SEM revealed a uniform morphology. FTIR spectra indicated the presence of carbonate, amine, hydrocarbon, and hydroxyl groups, suggesting residual organic substances such as protein, fat, and water. The uniform spectra across all samples highlight the consistency of the extraction process, ensuring a similar chemical composition.